Evaluating environmental flows for the targeted fish habitats in selected rivers - Md Abu Sayed; Aysha Akter (Heliyon)
This study aims to assess environmental flow (EF) to ensure fish habitats while serving as a drinking water source, determined as the Mean Annual Flow (MAF). The research estimates the EF requirements for fish populations and drinking water supply in the selected rivers, i.e., Padma, Karnafuli, and Halda, the primary water sources for Dhaka and Chattogram cities in Bangladesh. These rivers are renowned for their Hilsha and Carp fish habitats, which require specific water depths and Dissolved Oxygen (DO) levels for growth and survival. This study involves long-term field sampling, necessary onsite and laboratory tests, and historical secondary data analysis. The Hydrologic Engineering Centre's River Analysis System (HEC-RAS) was used to simulate the MAF and water quality of the studied sites. During the dry season at Mawa station, the flow of the Padma River drops below 20 % of the MAF, which could harm the river's aquatic life. However, DO levels in the studied stations have consistently remained above 6.0 mg/L. Conversely, the Halda and Karnafuli Rivers maintain a minimum water surface level of 2.35–2.40 m in the dry season. The DO levels in the Halda-Karnafuli River are below the acceptable limit each year. The flow of the Halda River decreases to less than 10 % of the MAF in the dry season, severely degrading the river's aquatic life and potentially hindering carp fish spawning. Thus, this study contributed to determining the EF of these rivers for Hilsha and Carp habitats, and this supports the Decision Support Systems (DSS).